2020
DOI: 10.1101/2020.12.08.416750
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comprehensive analysis of T cell immunodominance and immunoprevalence of SARS-CoV-2 epitopes in COVID-19 cases

Abstract: SUMMARYT cells are involved in control of SARS-CoV-2 infection. To establish the patterns of immunodominance of different SARS-CoV-2 antigens, and precisely measure virus-specific CD4+ and CD8+ T cells, we studied epitope-specific T cell responses of approximately 100 convalescent COVID-19 cases. The SARS-CoV-2 proteome was probed using 1,925 peptides spanning the entire genome, ensuring an unbiased coverage of HLA alleles for class II responses. For HLA class I, we studied an additional 5,600 predicted bindin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
158
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(174 citation statements)
references
References 54 publications
(112 reference statements)
12
158
1
Order By: Relevance
“…In this regard, a particular attention was allocated in our study to the B*07:02-restricted N105 epitope SPRWYFYYL. This epitope is of high interest as its immunodominance was experimentally demonstrated in many independent studies (Ferretti et al, 2020;Kared et al, 2021;Saini et al, 2021;Schulien et al, 2021;Sekine et al, 2020;Tarke et al, 2021). Precisely, we found a rare mutation consisting of PàS at P2 of this epitope (SPRWYFYYL à SSRWYFYYL).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In this regard, a particular attention was allocated in our study to the B*07:02-restricted N105 epitope SPRWYFYYL. This epitope is of high interest as its immunodominance was experimentally demonstrated in many independent studies (Ferretti et al, 2020;Kared et al, 2021;Saini et al, 2021;Schulien et al, 2021;Sekine et al, 2020;Tarke et al, 2021). Precisely, we found a rare mutation consisting of PàS at P2 of this epitope (SPRWYFYYL à SSRWYFYYL).…”
Section: Discussionsupporting
confidence: 64%
“…A comprehensive map of epitopes recognized by CD4+ and CD8+ T cell responses across the entire SARS-CoV-2 viral proteome was also recently reported (Tarke et al, 2020). Notably, the structural proteins Spike (S), Nucleocapsid (N) and Membrane (M) were shown to be rich sources of immunodominant HLAassociated epitopes, accounting for a large proportion of the total CD4+ and CD8+ T cell response in the context of a broad set of HLA alleles (Tarke et al, 2021). To date (May 2021), ~700 HLA class I-restricted SARS-CoV-2-derived epitopes have been experimentally validated (https://www.mckayspcb.com/SARS2TcellEpitopes/) (Quadeer et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The peptides used in our immunoassay predominantly stimulate CD4 + T cell responses, and cover all major immunodominant regions of the virus, including those in the spike, membrane and nucleocapsid proteins, as recently defined (26). TH1-type responses to these immunogenic regions were detected in the vast majority of convalescent SARS-CoV-2 infected and/or vaccinated individuals, in keeping with prior findings (26,27), although convalescent asymptomatic donors and a minority of naïve individuals demonstrate low-level reactivity. Prior studies have revealed the functionality and magnitude of adaptive immune responses to SARS-CoV-2 were significantly lower in mild cases of COVID-19 in comparison to severe (5), potentially the result of lower viral loads (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint (which this version posted April 26, 2021. ; https://doi.org/10.1101/2021.04.23.441209 doi: bioRxiv preprint cells 38 , could be associated with the escape from the T-cell immunity. Furthermore, recent evidence suggests that this region contains an additional epitope for antibody binding 39 .…”
Section: Insertions In the S Protein Produce Putative Antibody Escape Variantsmentioning
confidence: 99%